Corrosion protection of zinc coating on steels - Sofian, Azizul Helmi (2017)
Organic coated steel is widely used in industry because of well-known of its advantage towards corrosion protection. The objective is to understanding the physical appearances and behaviour of organic coating using SEM by investigate the internal reaction and environment nature. Three types of organic coating were used namely epoxy, zinc oxide and zinc primer spray paint to evaluate the effectiveness of coatings towards corrosion protection. There were four methods to identify the effectiveness of organic coating by mechanical testing including adhesion test, immersion test, temperature and thickness with different layer (1, 3, 5 layers). In addition, the kinetic growth can be analysed or interpret by using scanning electron microscope (SEM) for morphology observation. First, the samples mixed with solvent, ratio (1:1) and dry for 24 hours. After that, the sample were placed in hot area by taking the daily temperature and reference of humidity from Malaysia Meteorology Department. Besides that, cross-cut test was used to identify the good quality of adhesion. At the same times, samples were immersed in 3.5 % NaCl solution in duration at least 60 days. The thickness was measured by weighing before and after coating. The result for adhesion test for epoxy and zinc-epoxy shows high strength in chemical bonding. The weight percentage for all sample shows gain in weight but only one layer of zinc primer spray paint loss in weight. The temperature was lower for coated sample than uncoated sample. Lastly, the image of sample for immersion test were taken from SEM analysis. This research shows that zinc and epoxy act as anticorrosive protection barrier. The effectiveness of the coating thickness is recommended for future study.